Comparison between selective harmonic elimination and nearest level control for transistor clamped H-bridge inverter - Nurul Ain, Mohd Said; Abd Halim, Wahidah; Ali Saleh, Wail Ali; Jidin, Auzani (Institute Of Advanced Engineering And Science (IAES), 2022)
Total harmonic distortion (THD) is a key index used to measure the quality of output waveforms in multilevel inverters. In this paper the THD is investigated and compared between two modulation methods; selective harmonic elimination and nearest level control, for 13-level transistor clamped H-bridge (TCHB) inverter. The selected TCHB topology employs a reduced number of DC sources and switches compared with other conventional multilevel inverters, which helps to reduce the size and cost of the inverter. The performance of both modulation methods has been validated through simulations using MATLAB/Simulink. The results show that for selective harmonic elimination, the 13-level output exists for a narrow range of modulation index,